Cementing of an Empire - Laura Patricia Alvarez (Journal of Festive Studies)
In this photo essay on the Regias del Drag competition in Monterrey, Mexico, photographer Laura Alvarez meditates on the experiences, identities, and things that comprise northern Mexico’s queer communities.